Posture Analysis Using Nordic Body Map and Rapid Office Strain Assessment Methods to Improve Work Posture - Melia Agustin; Hendy Tannady; Octa Ferdian; Samuel Imanuel Gunawan Alamsjah (Universitas Bunda Mulia, 2021)
Jaya Launch Pad is a company engaged in educational services. It is undeniable that service sector companies such as Jaya Launch Pad also have a workforce whose work posture may be less ergonomic, which can lead to musculoskeletal disorders. Musculoskeletal disorders can be experienced by people of all ages. Therefore, this study focuses on work posture. This research occurred because of complaints experienced by staff. The number of samples used in this study was 1 person. This was influenced by the Covid-19 pandemic situation so that there was only 1 staff when the observation was made. The research method used was the nordic body map (NBM) to determine which parts of the body are experiencing complaints, and the rapid office strain assessment (ROSA) to measure the risk of injury due to the posture of sitting at a computer for 8 hours. The result is that the complaint assessment using the NBM questionnaire has a score of 52 (needs improvement at a later date) with 4 categories of severe pain, namely back, waist, buttocks, and buttocks. Meanwhile, the score from the ROSA table is 6 which means it is risky / dangerous so that it needs improvement. Therefore, a proposed condition is given in the form of a replacement of work facilities in the form of a work chair with adjustable height and adjustable armrests. This improvement is assumed to be able to reduce the level of staff complaints, and the calculation result of the rapid office strain assessment (ROSA) is 4 which means no risk so that this improvement is accepted and can solve the work posture problem of staff at Jaya Launch Pad.